Exploring the Neural Correlates of Metal Exposure in Motor Areas - Daniele Corbo; Roberto Gasparotti; Stefano Renzetti (Brain Sciences, 2025)
Background and objective: Environmental and occupational exposure to toxic metals poses a significant risk to neurological health, particularly affecting motor-related brain structures. Essential metals like manganese, copper, and iron become neurotoxic when homeostasis is disrupted, while non-essential metals such as lead, mercury, and cadmium are inherently toxic, even at low exposure levels. We aimed to investigate the state of the art on neuroimaging evidence of the effects of exposure to toxic metals on motor related brain structures and functions. Methods: PRISMA guidelines were followed. We included studies that reported neuroimaging studies exploring the link between metal exposure and neural changes in motor areas. Results: We identified 518 papers, but only 20 articles were included. Our findings indicate that manganese is the most extensively studied metal in relation to the motor system using neuroimaging, but studies have also investigated the effects of other metals, including lead, mercury, and copper. Across these studies, the brain regions most consistently affected by metal exposure include the globus pallidus, caudate nucleus, frontal cortex, and cerebellum. Some studies exhibit structural or functional reductions in these areas that correlate with increased levels of metal exposure, suggesting a dose-dependent neurotoxic effect. Conclusions: This review synthesizes current neuroimaging evidence on metal-induced neurotoxicity, emphasizing its impact on motor function and highlighting critical gaps to guide future research and public health strategies.